2020
DOI: 10.3390/biomedicines8090292
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Imidazoacridinone C-1311 is Effective in Androgen-Dependent and Androgen-Independent Prostate Cancer Cells

Abstract: The androgen receptor (AR) plays a critical role in prostate cancer (PCa) development and metastasis. Thus, blocking AR activity and its downstream signaling constitutes a major strategy for PCa treatment. Here, we report on the potent anti-PCa activity of a small-molecule imidazoacridinone, C-1311. In AR-positive PCa cells, C-1311 was found to inhibit the transcriptional activity of AR, uncovering a novel mechanism that may be relevant for its anticancer effect. Mechanistically, C-1311 decreased the AR bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Furthermore, recent studies revealed that C‐1311 facilitated the restoration of the DNA damage response cascade in androgen‐dependent prostate cancer cells. In contrast, C‐1311 targeted cellular metabolism and inhibited the genes responsible for the regulation of glycolysis and gluconeogenesis pathways in androgen‐independent prostate cancer cells 21 . Moreover, both compounds, C‐1305 and C‐1311 are selective inhibitors of cytochrome P450 (CYP) 1A2 and 3A4 isoenzymes 22,23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent studies revealed that C‐1311 facilitated the restoration of the DNA damage response cascade in androgen‐dependent prostate cancer cells. In contrast, C‐1311 targeted cellular metabolism and inhibited the genes responsible for the regulation of glycolysis and gluconeogenesis pathways in androgen‐independent prostate cancer cells 21 . Moreover, both compounds, C‐1305 and C‐1311 are selective inhibitors of cytochrome P450 (CYP) 1A2 and 3A4 isoenzymes 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, C-1311 targeted cellular metabolism and inhibited the genes responsible for the regulation of glycolysis and gluconeogenesis pathways in androgen-independent prostate cancer cells. 21 Moreover, both compounds, C-1305 and C-1311 are selective inhibitors of cytochrome P450 (CYP) 1A2 and 3A4 isoenzymes. 22,23 F I G U R E 6 The analysis of ERK1/2, Akt and p38α phosphorylation and expression in HCT116 tumour lysates.…”
Section: Discussionmentioning
confidence: 99%
“…Acronycine, a natural acridone alkaloid isolated from Acronychia baueri, has significant anticancer activities as a result of its interference in DNA replication of tumor cells [5,6]. A potent anticancer drug, C1311, which is in progress in clinical trials, can bind tumor DNA to inhibit the proliferation of cancer cells [7]. Moreover, several artificial acridone derivatives have acquired the antibacterial and anticancer abilities by incorporating an alkyl chain onto the N-position, such as with pyrimidocarvazones or pyrimidoacridone, respectively [8,9].…”
Section: Introductionmentioning
confidence: 99%